2020
DOI: 10.3390/metabo10020064
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Fluid Metabolomic Markers of Oligozoospermic Infertility in Humans

Abstract: Infertility affects 12–15% of couples worldwide, and male factors are the cause of nearly half of all cases. Studying seminal fluid composition could lead to additional diagnostic accuracy and a better understanding of the pathophysiology of male factor infertility. Metabolomics offers a new opportunity to evaluate biomarkers and better understand pathological mechanisms. The aim of the study was to identify new markers or therapeutic targets to improve outcomes in male factor or idiopathic infertility patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 46 publications
(45 reference statements)
3
42
0
Order By: Relevance
“…Previous metabolomic studies have also reported a significant decrease in various amino acids, including the ones we identified, in the seminal plasma of men with male factor infertility 12,43 . Among these amino acids, glutamate is the most abundant in the seminal plasma, and its concentration is correlated with the sperm concentration, 31 whereas aspartate is correlated with the number and motility of the sperm 16 . Both these amino acids have been repeatedly shown to be decreased in men with male factor infertility 7,14,16,42 .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Previous metabolomic studies have also reported a significant decrease in various amino acids, including the ones we identified, in the seminal plasma of men with male factor infertility 12,43 . Among these amino acids, glutamate is the most abundant in the seminal plasma, and its concentration is correlated with the sperm concentration, 31 whereas aspartate is correlated with the number and motility of the sperm 16 . Both these amino acids have been repeatedly shown to be decreased in men with male factor infertility 7,14,16,42 .…”
Section: Discussionsupporting
confidence: 65%
“…It has recently been used in the analysis of the seminal fluid in men with male factor infertility. However, there is a large heterogeneity in the methods used, the populations included, and the results reported, and no clear conclusion has been made so far 7‐16 . Moreover, the majority of these studies used the World Health Organization (WHO) reference values for sperm characteristics 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Mirnamniha et al [35] reported that the deficiency of trace elements such as calcium copper, manganese, magnesium, zinc, and selenium is associated with impaired spermatogenesis, altered levels of sex hormones, seminal oxidative stress, inflammation, and apoptosis. Recently, Murgia et al [12] detected altered levels of fructose, myo-inositol, aspartate, and choline in oligozoospermic men. In this paper, the data regarding the analyzed variables suggested some intriguing hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of other different semen biochemical components may explain their role in seminal pathologies. Recently, Murgia et al [ 12 ] indicated that seminal fluid metabolome may represent a marker for oligozoospermia. Moreover, the identification of the lipids most closely related to the reproductive success may be of great interest to the scientific community.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, amino acids, citric acid, choline, D‐glucose, myo‐inositol, lactate and pyruvate were significantly overexpressed in infertile teratozoospermic patients (Mehrparvar et al., 2020). In oligozoospermic patients, 1 H‐NMR detected altered levels of fructose, myo‐inositol, aspartate and choline, involved in the sperm maturation, energy metabolism and cell membrane composition (Murgia et al., 2020). Future in‐depth studies are required to better investigate the seminal metabolome and identify biomarkers associated with sperm abnormalities.…”
Section: Metabolomics and Male Reproductionmentioning
confidence: 99%